MADURESE DIALECTS' DIFFERENCES BETWEEN PROBOLINGGONESS AND MADURESE (SUMENEP) - Pranata, Mohammad Sofyan Adi (IJOEEL: International Journal of English Education and Linguistics, 2019)
This study employed descriptive qualitative design to obtain the data since this method focused on the result, not by the number of the subject. It was just by the real condition when the researcher conducted the research. This thesis identified, classified, and described the differences between Probolinggonese and Madurese dialect. In collecting the data, the researcher used some techniques, those were observation and interview. The result of research showed that there were differences in pronunciation, lexically, and syntactical between Probolinggonese and Madurese dialect. The differences of phonological were proved in pronunciation vowels a, i, u, e, o and some consonant differences. In the lexical point of view, it was proved based on pronoun, adjective, verb, adverb, noun, and conjunction. From syntactical point of view, Probolinggonese and Madurese dialects had adding suffix, affix, and intrusive sound.